Acculturation and use of health care services by Turkish and Moroccan migrants: a cross-sectional population-based study - Hesselink Arlette E; Fassaert Thijs; Verhoeff Arnoud P (BMC, 2009)
Abstract Background There is insufficient empirical evidence which shows if and how there is an interrelation between acculturation and health care utilisation. The present study seeks to establish this evidence within first generation Turkish and Moroccan migrants, two of the largest migrant groups in present-day Western Europe. Methods Data were derived from the Amsterdam Health Monitor 2004, and were complete for 358 Turkish and 288 Moroccan foreign-born migrants. Use of health services (general practitioner, outpatient specialist and health care for mental health problems) was measured by means of self-report. Acculturation was measured by a structured questionnaire grading (i) ethnic self-identification, (ii) social interaction with ethnic Dutch, (iii) communication in Dutch within one's private social network, (iv) emancipation, and (v) cultural orientation towards the public domain. Results Acculturation was hardly associated with the use of general practitioner care. However, in case of higher adaptation to the host culture there was less uptake of outpatient specialist care among Turkish respondents (odds ratio [OR] = 0.90, 95% confidence interval [CI] = 0.82-0.99) and Moroccan male respondents (OR = 0.81, 95% CI = 0.71-0.93). Conversely, there was a higher uptake of mental health care among Turkish men (OR = 0.81, 95% CI = 0.71-0.93) and women (OR = 0.81, 95% CI = 0.71-0.93). Uptake of mental health care among Moroccan respondents again appeared lower (OR = 0.74, 95% CI = 0.55-0.99). Language ability appeared to play a central role in the uptake of health care. Conclusion Some results were in accordance with the popular view that an increased participation in the host society is concomitant to an increased use of health services. However, there was heterogeneity across ethnic and gender groups, and across the domains of acculturation. Language ability appeared to play a central role. Further research needs to explore this heterogeneity into more detail. Also, other cultural and/or contextual aspects that influence the use of health services require further identification.